GONTOR'S ARABIC VARIATION: A STUDY OF ARABIC LANGUAGE USE BY ALUMNI OF GONTOR MODERN ISLAMIC BOARDING SCHOOL ON SOCIAL MEDIA (SOCIOLINGUISTIC STUDIES) - Afnan Arummi; Alif Cahya Setiyadi (Arabic Literature Department, 2022)
This paper examines the variations of Gontor's Arabic style through a sociolinguistic approach. The objective of this study is to describe the styles of Arabic used by Pondok Modern Gontor (PMG) alumni on the social media platforms WhatsApp (WA) and Facebook (FB). The data in this paper were collected by the listening method from daily conversations of alumni on social media, and then continued through download and record techniques. The collected data were analyzed using contextual techniques. This study was successful in identifying the peculiarities of Gontor-style Arabic use by PMG alumni in social media, which manifest in several variations, including (1) verbal forms such as shortening (contractions), acronyms, and greetings; (2) the use of speech styles such as speech styles with polysemous expressions, speech styles using synonymous words, and speech styles with code-mixing; and (3) the specificity of linguistic forms consisting of Arabic vocabularies used and understood by fellow PMG alumni.